2017
DOI: 10.1016/j.yebeh.2017.03.004
|View full text |Cite
|
Sign up to set email alerts
|

How do you exercise with epilepsy? Insights into the barriers and adaptations to successfully exercise with epilepsy

Abstract: Exercise has been shown to be a physiological and psychological benefit for people with epilepsy (PWE). However, barriers prevent many PWE from exercising safely and confidently. This research explored current perceived barriers to exercise and adaptation techniques used by PWE in order to maintain physical activity levels. Three focus groups (2-3 participants per group) and three semi-structured interviews were conducted (11 participants total). Constructive grounded theory was used to frame the study and ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 22 publications
1
21
0
Order By: Relevance
“…For example, it is unknown whether there are differences in physical activity and sedentary levels between different subtypes of epilepsy, between people with active and inactive epilepsy and between people with epilepsy with and without mental and/or physical co-morbidity. Previous individual studies have demonstrate that presence of co-morbid anxiety and depression [19][20][21], fear of exercise-induced seizures [22], sideeffects of antiepileptic drugs [19], and perceived stigma [23,24] contribute to lower physical activity levels in people with epilepsy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, it is unknown whether there are differences in physical activity and sedentary levels between different subtypes of epilepsy, between people with active and inactive epilepsy and between people with epilepsy with and without mental and/or physical co-morbidity. Previous individual studies have demonstrate that presence of co-morbid anxiety and depression [19][20][21], fear of exercise-induced seizures [22], sideeffects of antiepileptic drugs [19], and perceived stigma [23,24] contribute to lower physical activity levels in people with epilepsy.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the benefits of an active lifestyle, people with epilepsy experience a range of barriers to engaging in more physical activity and becoming less sedentary, such as the presence of co-morbid anxiety and depression [19][20][21], fear of exercise-induced seizures [22], side-effects of antiepileptic drugs such as drowsiness, fatigue, headache or migraine, gastrointestinal disturbances, dizziness and faintness, rash or skin disorders [19] and perceived stigma [23,24]. Given that an active lifestyle is related to a better seizure control and quality of life in people with epilepsy, understanding physical activity and sedentary levels among people with epilepsy is critical to improving long-term health outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Social support can provide encouragement and may help overcome perceived barriers to exercise 12. Young people should be encouraged to take regular physical exercise, including contact sports if they wish, and be supervised for water sports, harnessed climbing, and horse riding 13.…”
Section: How Should Families Approach Sports and Exercise?mentioning
confidence: 99%
“…In all, 17 studies investigated the effect of physical activity on comorbidities such as anxiety and depression, as well as quality of life. Ten of these studies ("2−" n = 8, "3" n = 2; survey-/interview-based studies, combined studies, studies on one-time physical effort) showed physical activity to have a positive effect (4, 9,12,14,[16][17][18][19][20][21]. The results of six interventional studies (n = 2 evidence-level "1-", n = 4 "2−") revealed a similar picture.…”
Section: Resultsmentioning
confidence: 97%
“…• Epidemiological study with 1 173 079 male conscripts aged 18 and "2+") referred to in this review are additionally shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%